Bully Anak Artis Lesti Kejora dalam Analisis Wacana Kritis Norman Fairclough - Wahyuni Siregar; M. Surip; Syairal Fahmy Dalimunthe (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
This article describes Fairclough’s normative critical discourse on physical insults to children with Lesti Kejora using Norman theory. The method used in this research is descriptive qualitative method, listening method and literature study. The observation method was also applied in this study. This study also uses a note-taking approach. The survey consists of three phases: a data acquisition phase, a classification phase, and a data analysis phase. This study uses two news media, Suara.com and Herstory, based on the analysis of Fairclough's theory, bullying the child of artist Lesti Kejora. The data analysis technique used is reducing data, presenting data, and drawing conclusions. The purpose of the study was to find out how the two SH media (Suara.com and Herstory.ac.id) obtained information about the physical insults of Lesti Kejora's children. The theory used in this study is a three-dimensional model from Norman Fairclough, namely the micro, mesostructural, and macrostructural dimensions. Microstructural analysis that describes the negative and positive sides of physical abuse of children with Lesti Kejora, mesostructurally how the media obtains information related to physical abuse of children. Social situations depicting children's physical appearance as monkeys are associated with children's physical humiliation.